[2(x+y)^2]/[2(x-y)^2]

=(x+y)^2/(x-y)2

=[(x-y)^2+4xy]/(x-y)^2

=1+4/(x-y)^2

=1+4/(x-1/x)^2

x can be anything. Without knowing the value of x or y, there is no single answer to this problem, unless my reading of the question is not correct. The strangest thing is why there's the two 2s in both the denominator and numerator. Seems like there's a typo somewhere.

_________________

Keep on asking, and it will be given you;

keep on seeking, and you will find;

keep on knocking, and it will be opened to you.